Analysis of the Implementation of Syariah Home Ownership Credit (KPR) Financing With the Murabahah Agreement at Bank Syariah Indonesia KCP Medan Juanda - Sari, Chyntia Kemala; Sriwardany, Sriwardany; Irama, Ova Novi; Munawarah, Wilda Sri (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Sharia mortgage shows that sharia banking is currently developing very well. In general, sharia banks are institutions that function to receive and distribute community funds but with sharia principles. In receiving or distributing financing to the community, there are many contracts used in sharia banks. Such as mudharabah, wadiah, murabahah, etc. However, for the distribution of financing to the community, sharia banks generally use the murabahah sale and purchase contract. This study aims to determine the application of the murabahah contract in sharia mortgage financing at Bank Syariah Indonesia Kcp Medan Juanda on Jl. l. Ir. H. Juanda No.3a, Ps. Merah Bar., Kec. Medan City. To determine the application of the contract in accordance with the fatwa of the National Sharia Council of the Indonesian Ulema Council. This type of research uses a qualitative descriptive method and in collecting data, this type of research uses a case study approach. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The data validity test used in this study is the credibility test. The results of this study indicate that; The risks that occur at Bank Syariah Indonesia KCP Medan Juanda in financing Sharia KPR using the murabahah contract are financing risk, operational risk, market risk and liquidity risk caused by events originating from internal (Bank Syariah Indonesia KCP Medan Juanda Mada) and external banks ( customers and markets). The implementation of risk management at Bank Syariah Indonesia KCP Medan Juanda is carried out by identifying risks, measuring risks using the 5C Credit Analysis method, monitoring risks, and controlling risks. In addition, these regulations are in accordance with the Company's Internal SOP and the regulations of the Financial Services Authority.